Diversity and taxonomy of the genus Unio Philipsson in Italy, with the designation of a neotype for Unio elongatulus C. Pfeiffer (Mollusca, Bivalvia, Unionidae) - Marrone, Federico; Nardi, Gianbattista; Cianfanelli, Simone; Govedič, Marijan; Barra, Salvatore Alessandro; Arculeo, Marco; Bodon, Marco (Zootaxa, 2019)
Novel Unio spp. populations from Slovenia, the Italian peninsula, Sardinia and Sicily were genetically analysed in order to define the distribution and diversity of the genus Unio in Italy and neighbouring areas. The presence of two primarily allopatric autochtonous species, Unio elongatulus Pfeiffer, and Unio mancus Lamarck, is confirmed for the Italian peninsula, Corsica, Sardinia, and Sicily. Autochthonous populations of Unio elongatulus are present in the peri-Adriatic drainages of the Italian and Balkan peninsulas, south as far as the Ofanto River (Apulia, Italy) and Lake Skadar (Albania), while its presence in the Tyrrhenian rivers of Tuscany is likely due to anthropogenic introduction events. Conversely, Unio mancus turtonii Payraudeau, an endangered peri-Tyrrhenian taxon, was found with autochthonous populations in the Apennine-Tyrrhenian drainages of peninsular Italy, eastern Mediterranean France, Corsica, Sardinia and Sicily, while the actual autochthony of the single population found in the Ionian basin of the Italian peninsula (Bradano River, Basilicata) deserves further investigation. The Italian population of U. mancus requienii Michaud, reported from Lake Montepulciano is to be considered allochthonous. The binomen U. elongatulus, although widely used in the recent scientific literature, was, to date, assigned to a doubtful species, because its type locality includes a large area inhabited by different Unio taxa, which are not clearly distinguishable by their shell alone; furthermore, no type material is present in historical collections. To retain the recently-used name, a new restricted type locality is established, where only U. elongatulus lives, and a neotype is designated. The validity of the subspecies of Unio mancus is also discussed and confirmed. Finally, hypotheses on the origin of Italian mussels, and considerations on their conservation status are discussed.